2021
DOI: 10.1038/s41467-021-25638-9
|View full text |Cite
|
Sign up to set email alerts
|

Polymerized small molecular acceptor based all-polymer solar cells with an efficiency of 16.16% via tuning polymer blend morphology by molecular design

Abstract: All-polymer solar cells (all-PSCs) based on polymerized small molecular acceptors (PSMAs) have made significant progress recently. Here, we synthesize two A-DA’D-A small molecule acceptor based PSMAs of PS-Se with benzo[c][1,2,5]thiadiazole A’-core and PN-Se with benzotriazole A’-core, for the studies of the effect of molecular structure on the photovoltaic performance of the PSMAs. The two PSMAs possess broad absorption with PN-Se showing more red-shifted absorption than PS-Se and suitable electronic energy l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
174
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(174 citation statements)
references
References 57 publications
0
174
0
Order By: Relevance
“…Li et al reported polymer acceptor PN-Se and they use cryogenic transmission electron microscopy to study the aggregation behavior of the PBDB-T donor and the polymer acceptor. 104 Then they found that a bicontinuous-interpenetrating network with aggregation size of 10–20 nm and this was very favourable for the charge transfer and a high PCE of 16.16% was achieved in the OSCs. These results indicate that FREA polymerisation is a promising strategy to develop highly efficient polymers for all-PSCs.…”
Section: The Development Of New Donor and Acceptor Materials In The Oscsmentioning
confidence: 99%
“…Li et al reported polymer acceptor PN-Se and they use cryogenic transmission electron microscopy to study the aggregation behavior of the PBDB-T donor and the polymer acceptor. 104 Then they found that a bicontinuous-interpenetrating network with aggregation size of 10–20 nm and this was very favourable for the charge transfer and a high PCE of 16.16% was achieved in the OSCs. These results indicate that FREA polymerisation is a promising strategy to develop highly efficient polymers for all-PSCs.…”
Section: The Development Of New Donor and Acceptor Materials In The Oscsmentioning
confidence: 99%
“…[24][25][26] In recent years, the efficiency of all-PSCs have also significantly improved owing to material innovation and device engineering, thereby strongly substantiating their prospects and research value. [25][26][27][28][29][30] With over 16% PCE [31][32][33][34] and > 1 year lifetime [35] achieved in laboratory (with a spin-coating strategy), more effort is required to scale the fabrication. [5,36] Solution printing is widely recognized as one of the costeffective, large-area, and facile preparation techniques for film deposition.…”
Section: Introductionmentioning
confidence: 99%
“…[ 24–26 ] In recent years, the efficiency of all‐PSCs have also significantly improved owing to material innovation and device engineering, thereby strongly substantiating their prospects and research value. [ 25–30 ] With over 16% PCE [ 31–34 ] and > 1 year lifetime [ 35 ] achieved in laboratory (with a spin‐coating strategy), more effort is required to scale the fabrication. [ 5,36 ]…”
Section: Introductionmentioning
confidence: 99%
“…Organic solar cells (OSCs) based on polymer acceptors attract considerable attention for potential commercial application because of their superior thermal and light stability, and excellent efficiency. 1–11 The energy loss for the polymer acceptor could also be as low as 0.47 eV. 6,8 Importantly, the polymer acceptor could be easily polymerized from the small acceptors, and their opto-electrical properties could be well tuned through the monomer or ternary copolymerization.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,12–14 Consequently, the power conversion efficiency (PCE) has surpassed 16% for the binary all-polymer OSCs and reached 17% for ternary all-polymer OSCs. 11,15 Adopting all the merits of polymer acceptors, however, the OSCs using the combination of polymer acceptors and small molecule donors (SM D /P A -type) have attracted less attention than other systems. 16,17 In 2019, Wang et al exhibited excellent thermal stability of SM D /P A -type OSCs.…”
Section: Introductionmentioning
confidence: 99%